Identification of Suitable Mulch for Radish (Raphanus sativus L.) to Cope with Temperature Stress - Kumara, R.P.D.N.; Rasanjali, K.G.A.I.; De Silva, C.S. (University of Jaffna, 2019)
Although mulching provides numerous benefits in cropping activities, very few studies were reported on crop specific influence of different mulching materials. Thus, a pot experiment was conducted in a polytunnel to assess impact of different mulching materials on growth and yield of radish (cultivar, Beeralu). Treatments were arranged in two-factorial experiment in Completely Randomized Design with three replicates. Two temperature regimes viz. ambient (32-33°C) and temperature stress (35-36°C) condition and three types of mulching materials viz. coir dust (M2), gliricidia (M3) and straw (M4) were used as treatments. Crops without a mulch was the control (M1). Raddish seeds were sown in pots filled using reddish brown earth soil. One week after the emergence of seedlings, mulching materials were applied according to treatments. Growth parameters (number and fresh weight of leaves) and yield parameters (root fresh weight, root dry weight, root length and girth of the root) were measured. Data were statistically analyzed using SAS and mean separation was done by Least Significant Difference test. The results revealed that the temperature and mulching material and their interaction were significantly (p<0.05) influenced on most of growth and yield parameters tested. Highest number of leaves (17.2), leaf fresh weight (59.8 g), plant height (45.1 cm), length of tuber (16.1cm), fresh weight of tuber (77.3 g) and dry weight of tuber (18.8 g) were recorded in gilicidia mulch under the temperature stress. Coir dust mulch under the ambient temperature indicated the second best performance among the tested treatments. Lowest performance in raddish crop was recorded in temperature stress condition without having a mulch.
Keywords: Growth; Mulch; Temperature; Yield